The impact of preoperative venous thromboembolism on patients undergoing TURBT: Perioperative outcomes and healthcare costs from US insurance claims data - Anas S. Tresh; Francesco Del Giudice; Shufeng Li; Satvir Basran; Ettore De Berardinis; Dalila Carino; Valerio Santarelli; Bernardo Rocco; Maria Chiara Shighinolfi; Roman Mayr; Matteo Ferro; Riccardo Autorino; et al. (BJUI Compass)
Abstract Objectives To assess the impact of a positive history of venous thromboembolism (VTE) on perioperative outcomes, including length of in‐hospital stay, readmission rates, 90‐day postoperative complications, and healthcare costs in bladder cancer (BCa) patients undergoing transurethral resection of bladder tumour (TURBT) in the United States. Patients and Methods Patients aged ≥18 years with a BCa diagnosis undergoing TURBT were identified in the Merative® Marketscan® Research de‐identified databases between 2007 and 2021. Multivariable logistic regression adjusted by relevant perioperative confounders was used to investigate the association between diagnosis of VTE before TURBT and 90‐day complication rates, new postoperative VTE events, re‐hospitalization, and total hospital expenditures (2021 US dollars). Sensitivity analyses on VTE severity (pulmonary embolism [PE], deep venous thrombosis [DVT] or superficial thrombophlebitis/phlebitis [SVT]), as well as TURBT extent (minor vs. major) were additionally examined. Results In total, 139 800 patients were identified, with 5.3% having preoperative VTE, including DVT (n = 3112, 42.20%), PE (n = 2046, 27.74%) and SVT (n = 2217, 30.06%). A history of preoperative VTE predicted higher rates of any complication (adjusted odds ratio [aOR] 1.28, 95% CI 1.14–1.43) and also higher rates of infectious and haemorrhagic complications. Additionally, preoperative VTE increased the risk of novel VTE events following TURBT (aOR 17.30, 95% CI 16.05–18.65), hospital length of stay (aOR 2.23, 95% CI 1.90–2.62), readmissions (aOR 1.47, 95% CI 1.39–1.56), and hospital associated costs (aOR 1.17, 95% CI 1.12–1.23). DVT and non‐minor TURBT procedures did not increase the risk of any, infectious, or haemorrhagic complications, but other associations were maintained regardless of the severity of VTE (PE, DVT, SVT) or TURBT extent (minor/major). Conclusions A history of VTE before undergoing transurethral procedures for BCa is associated with significantly worse perioperative outcomes and higher healthcare costs. These findings may help us to counsel on the risks of the intervention and hopefully improve our ability to mitigate such risks.